(untitled) (UNIZIK Journal of Marketing, 2024)
Global marketing dynamics profoundly influence viral strategies, reshaping international business operations. The increasing complexity of global markets has posed new challenges for managing cross-border activities. This study aimed to assess the influence of global marketing dynamics on viral strategies. Technological presence and cultural content were used as indicators of global marketing dynamics, while social media and email marketing served as proxies for viral strategies. A descriptive survey approach was employed, targeting employees of three multinational corporations in Lagos State, Nigeria. The study’s population comprised 1,152 employees from Coca-Cola, Nestlé, and Guinness Nigeria, with a sample size of 297 respondents. The proposed hypotheses were tested using z-test statistics. The results indicated that technological presence significantly enhances social media viral strategy (z = 10.345, p < 0.05), and cultural content positively affects email viral strategy (z = 8.712, p < 0.05). The findings imply that multinational corporations in Nigeria can optimize their marketing efforts by enhancing their technological presence to boost social media viral strategies, while tailoring culturally relevant content to improve the effectiveness of email viral strategies, ultimately driving higher engagement and localization in their campaigns. Therefore, the study confirmed that global marketing dynamics have a substantial impact on viral strategies. It is recommended that companies aiming to optimize their social media viral strategies should prioritize technological advancements and invest in cutting-edge digital tools to enhance their online presence. Additionally, businesses should incorporate culturally relevant content into their email marketing strategies to foster stronger connections with diverse international audiences, ultimately boosting engagement and campaign effectiveness.